Efisiensi Anggaran Belanja Pada Dinas Energi Dan Sumber Daya Mineral Provinsi Nusa Tenggara Timur - Theresia Fouk Leu; Aletha Maria Nenabu (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The problem in this study is that the realization of spending in 2020-2023 did not reach the setting budget that was completed and in 2021 the realization of spending declined, but did not provide an overview of how the budget efficiency at the ESDM Office during 2020-2023. The purpose of this study is to know the efficiency of the direct expenditure budget at the Department of Energy and Mineral Resources of East Nusa Tenggara Province. Data collection techniques used in this study are interviews and documentation. Data analysis techniques in this study are quantitative descriptive by using direct expenditure efficiency ratios. The results of the calculation of the ratio of direct expenditure efficiency of the NTT Provincial ESDM Office during 2020-2023 amounted to 94.88% which is included in the "Efficient" category of Calculation of Direct Expenditure Efficiency Ratios in 2020 NTT Province ESDM Office of 92.24% with Efficient Criteria, Results of Calculation of Direct Expenditure Efficiency Ratios in 2021 2022 NTT Province ESDM Office of 89.11 with efficient criteria, the results of the calculation of the ratio of direct spending efficiency in 2023 NTT Province ESDM Office of 95.95% with efficient criteria. It is recommended that the ESDM Service maintain the efficiency achieved by continuously ensuring that all expenditures are truly targeted and provide direct benefits to the community. For other researchers, it is hoped that this thesis can serve as a reference for other researchers who will conduct further research on the same substance in more depth. Keywords: Budget Efficiency, Direct Expenditure, Efficiency Ratio, Budget Realization, Descriptive Quantitative Analysis, Public Sector Finance, Energy and Mineral Resources Office, East Nusa Tenggara